Pendampingan Upgrading Perpustakaan Ngudi Ilmu Desa Warungpring Pemalang - Prabowo, Dimas Setiaji; F, Fatchurohman; Khasanah, Faiza Alfa; Prayogi, Arditya; Shilla, Rhischa Assabet (Nanggroe: Jurnal Pengabdian Cendikia, 2024)
One of the main causes of low reading and writing skills in Indonesia is the lack of access to books and adequate reading facilities. The availability of reading books and facilities at the Ngudi Ilmu Library in Warungpring Village, Pemalang is still very limited, resulting in low community literacy. Community service by the KKN Team 16 UIN K.H. Abdurrahman Wahid Pekalongan in the form of upgrading the Ngudi Ilmu Library in Warungpring Village, Pemalang. The method of implementing this service uses a participatory method involving the KKN Team 16, the village, and the Warungpring community itself. The form of community service packaged in the Ngudi Ilmu Library upgrading program is divided into eight activities including, Coordination with the Village regarding the Library Upgrading plan, Field Observation regarding the condition of the Library, Implementing Library Cleanliness, Inventorying Library Books, Conducting Open Book Donations, Adding Books and Library Collections, Rearranging the Library, and Symbolic Inauguration of the Ngudi Ilmu Library in Warungpring Village.